Determinant Factors of Nurse's Compliance with Prevention of Application Standards in Health Care Associated Infection (HAIS) Prevention Effort in ICU And UGD Kendari Hospital. - Astrina Prihandini Juspar; Narmi Narmi; Narmawan Narmawan (KLASICS, 2022)
Absctract. Health Care Associated Infection (HAIs) is hospital acquired infections both of which occur in patients when receiving treatment, health workers who work in hospitals and hospital visitors. Standar Precaution created to protect against accidents that can occur. The application of the precaution standard is influenced by compliance. The purpose of knowing the determinants of nurses' adherence to the implementation of Precaution Standards in the prevention of HAIs in the Intensive Care Unit and Emergency Room at the Kendari City Hospital. The type of research used is correlation analytic using the Cross Sectional Study approach. The sample were 37 ICU and IGD room nurses. The sampling technique uses total sampling technique. The variables studied consisted of the dependent variable that is the application of the precaution standard and the independent variables namely knowledge, availability of facilities and motivation. The analysi used is Spearman's rho. The results showed that there is a relationship of knowledge (ρ=0,002; r=0,491), availability of facilities (ρ =0,006; r=0,444) and motivation (ρ =0,009; r=0,425) by applying the precaution standard in the prevention of HAIs. The conclusion of this study is that there is a relationship between knowledge of the availability of facilities and motivation with the application of precaution standards in efforts to prevent HAIs. It is recommended to nurses to increase awareness, understanding, and insight into the quality of nursing services in implementing standard precaution so that the incidence of HAIs can be minimized or prevented.